2014
DOI: 10.1080/14789949.2014.903505
|View full text |Cite
|
Sign up to set email alerts
|

Associations between ward climate and patient characteristics in a secure forensic mental health service

Abstract: Ward climate is associated with patient satisfaction and, potentially, with improved outcomes but increased understanding of its relationship with individual patient characteristics is required. We investigated relationships between patient (N = 63) gender, perceived risk, risk behaviour, therapeutic engagement (session attendance), psychopathology and ward climate in a forensic psychiatric hospital. Lower security levels were significantly associated with better patient cohesion (PC), experienced safety (ES) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
32
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 42 publications
7
32
4
Order By: Relevance
“…In contrast to Dickens et al (2014) there is also research showing that patient characteristics have a small or no impact on ward climate (Moos, 1997;Pedersen & Karterud, 2007). Pedersen and Karterud (2007) found no substantial associations between patient characteristics (gender, age, level of education, self reported symptom distress, interpersonal problems, diagnosis) and individual ratings of treatment milieu.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…In contrast to Dickens et al (2014) there is also research showing that patient characteristics have a small or no impact on ward climate (Moos, 1997;Pedersen & Karterud, 2007). Pedersen and Karterud (2007) found no substantial associations between patient characteristics (gender, age, level of education, self reported symptom distress, interpersonal problems, diagnosis) and individual ratings of treatment milieu.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, Howells et al (2009) found that patients in a high secure hospital service in the United Kingdom (UK) evaluated cohesion among patients more favorably than staff members. Another study found that patients in open, low and medium secure wards of a psychiatric hospital in the UK evaluated the ward climate as safer than staff members (Dickens et al, 2014). In both studies, staff members evaluated the therapeutic hold (how much the environment is supportive of therapy and therapeutic change) more favorably compared to patients.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations